2017
DOI: 10.1007/s11191-017-9900-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinism in the Genetics Curriculum

Abstract: Twenty-first-century biology rejects genetic determinism, yet an exaggerated view of the power of genes in the making of bodies and minds remains a problem. What accounts for such tenacity? This article reports an exploratory study suggesting that the common reliance on Mendelian examples and concepts at the start of teaching in basic genetics is an eliminable source of support for determinism. Undergraduate students who attended a standard 'Mendelian approach' university course in introductory genetics on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 54 publications
0
66
0
6
Order By: Relevance
“…In response to these findings, Castéra et al (2013) suggested that approaching discussions of genetic determinism through philosophy (vs. content knowledge alone) might be a more effective approach for altering students' thinking about genetic determinism. Similarly, Jamieson and Radick (2017) suggested approaching genetics education from a novel perspective. They found that by comparing two groups of undergraduate students, one taking a classical genetics course based on Mendelian genetics and the other taking a course based on developmental processes and their role in bringing about phenotypic variation, the students in the latter group were less deterministic about genes (Jamieson and Radick 2017).…”
Section: The Relationship Between Knowledge and Belief In Genetic Detmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to these findings, Castéra et al (2013) suggested that approaching discussions of genetic determinism through philosophy (vs. content knowledge alone) might be a more effective approach for altering students' thinking about genetic determinism. Similarly, Jamieson and Radick (2017) suggested approaching genetics education from a novel perspective. They found that by comparing two groups of undergraduate students, one taking a classical genetics course based on Mendelian genetics and the other taking a course based on developmental processes and their role in bringing about phenotypic variation, the students in the latter group were less deterministic about genes (Jamieson and Radick 2017).…”
Section: The Relationship Between Knowledge and Belief In Genetic Detmentioning
confidence: 99%
“…Similarly, Jamieson and Radick (2017) suggested approaching genetics education from a novel perspective. They found that by comparing two groups of undergraduate students, one taking a classical genetics course based on Mendelian genetics and the other taking a course based on developmental processes and their role in bringing about phenotypic variation, the students in the latter group were less deterministic about genes (Jamieson and Radick 2017). Clearly, more work is needed in order to better understand the relationship between forms of genetics education and beliefs in genetic determinism.…”
Section: The Relationship Between Knowledge and Belief In Genetic Detmentioning
confidence: 99%
“…Proponents of developmental systems biology highlighted that genes by themselves do not lead to phenotypes, but rather genes are one among many causal factors or resources, embedded in contexts rich in other Causal mapping as a teaching tool for reflecting on causation in human evolution ---Preprint --resources that are also often causal factors in the development, or reconstruction , of particular phenotypes (Griffiths & Gray, 1994;Oyama et al, 2001). This basic yet important insight is also being recognized among genetics education researchers (Jamieson & Radick, 2017). In humans in particular, many observable phenotypes cannot be explained solely by genetic causation, such as language, tool making, literacy, personality, or occurrence of particular diseases.…”
Section: Teleological Reasoning In Different Types Of Causal Explanationmentioning
confidence: 90%
“…Our philosophy of place (combined with Jung and Lacan) opposes the idea that "genes invariably determine characters, so that the outcomes are just a little, or not at all, affected by changes in the environment or by the different environments in which individuals live" (Jamieson, Radick, 2017, p. 1265. We believe this because "any place encompasses other places within it while also being encompassed by other places in its turn" (Malpas, 2012, p. 49) and this is not recognised when an individual is reduced to their genes.…”
Section: Genetic Determinism Place and Human Charactermentioning
confidence: 99%
“…We believe this because "any place encompasses other places within it while also being encompassed by other places in its turn" (Malpas, 2012, p. 49) and this is not recognised when an individual is reduced to their genes. An important reason why this is problematic is that it can lead to 'genetic optimism', which is the belief "that increased understanding of genes, and greater ability to manipulate them, will be a 'super solution', especially in relation to human health and medical developments" (Jamieson, Radick, 2017, p. 1266. This optimism is misguided because it overlooks the importance of factors such as place and without this recognition; an individual will continue to experience mental illness through obstructive complexes (Gildersleeve, Crowden, 2018).…”
Section: Genetic Determinism Place and Human Charactermentioning
confidence: 99%